Rock Creek Bridge documentation, - Emerson, Stephen
The seventy year old Rock Creek Bridge No. 3304 (Spokane County) was replaced in 2003, having failed to meet safety standards. It did not meet the criteria for listing on the national register of historic places, but the Spokane County Division of Engineering and Roads believed it was worthy of documentation in the eventuality of removal. The photographs and documentation were made for that purpose. The documentation includes a map showing the location and photographs.